Pedogenesis and Classification of Soils in Banten, West Java, Indonesia - Isa, Achmad Fauzi (2002)
Sods on three toposequences In Anyer, Canta and Saketi areas In Banten Province, West Java, and soil on Rakata Island (Krakatau volcano) m Sunda Strait, IndoneSIa have been sampled for pedogenetic study and classification The soils in Banten developed on the slope of the Quaternary volcanic complex and the sedimentary facies with different annual rainfall and vegetation The objectives of this study were to determine the soil physical, chemical, mineralogical and micromorphological properties, to study the genesis of the solis, to determine the effects of the Krakatau ash and to classify the soils according to soil Taxonomy and World Reference Base the result showed that all the soils on the slope of volcanic complex have been strongly weathered to form yellowish brown to red deep soils With high clay content, low pH, low base and various CEC Mineralogical characteristics of these soil consist of dominant kaolinite In the clay fractions, crystobalite and quartz In the silt fractions and opaque minerals In the sand fractions T he mineralogical characteristics indicate that most of the soils may be formed from andesitic volcanic ash The relative higher amount of weatherable minerals with pumice in the surface horizon confirmed that the soils were rejuvenated by fresh volcanic ash from the eruption of Krakatau volcano in 1883. The efTects of the Krakatau ash were not shown at the soils on the lower slope of the Saketi toposequence. These soils developed from sedimentary facies which were comprised of acid tuff, claystone and sandstone. These soils are characterised by yellowish brown colour, clay textured B horizons with various sand content with depth, low pH, low base and various CEC.